Facile synthesis of amine-functionalized SBA-15-supported bimetallic Au–Pd nanoparticles as an efficient catalyst for hydrogen generation from formic acid. Issue 8 (17th January 2017) - Xu, Lixin; Yao, Fang; Luo, Jili; Wan, Chao; Ye, Mingfu; Cui, Ping; An, Yue
Abstract : Superior catalytic activity arises from synergy between Au–Pd and SBA-15-Amine. Abstract : In this study, a series of amine-functionalized SBA-15-supported bimetallic Au–Pd nanoparticles (Au–Pd/SBA-15-Amine) as catalysts are successfully synthesized by surface functionalization and co-reduction and characterized by inductively coupled plasma-atomic emission spectroscopy, XRD, XPS, and TEM. The Au–Pd/SBA-15-Amine catalysts thus obtained are tested for the dehydrogenation of formic acid (FA)–sodium formate (SF). Among the tested Au–Pd/SBA-15-Amine catalysts, as-synthesized Au2 Pd8 /SBA-15-Amine exhibits 100% H2 selectivity and outstanding catalytic activity with an initial turnover frequency (TOF) of 1786 h −1 at 323 K; this superior catalytic activity is attributed to synergy between Au–Pd and SBA-15-Amine and the promotion effect of SF. At SF concentrations of greater than 0.5 mol L −1, SF can partially participate in dehydrogenation. The facile synthesis of the Au–Pd/SBA-15-Amine catalyst is imperative for accelerating the widespread application of FA–SF mixtures as a promising hydrogen carrier.